Seasonal changes in power of competitive cyclists: implications for monitoring performance - Paton, C. D.; Hopkins, W. G. (Journal of Science and Medicine in Sport, 2005)
Sport scientists should consider seasonal trends and individual variability in performance when using tests to track performance changes resulting from training or other medium-term interventions with individuals or in research studies. We report here the seasonal changes and variability in power of 12 male competitive cyclists, who performed laboratory tests of incremental peak and 4-km mean power measured with three ergometers simultaneously in each of five sessions during three phases (base, pre-comp, comp) of a season. Repeated-measures analysis of log-transformed power provided mean percent changes in performance between phases and within-cyclist variability in performance expressed as coefficients of variation between sessions < or = 2 wk apart within a phase and between sessions 8 wk-12 wk apart in different phases. Peak power increased from the base phase to the pre-comp phase on average by 5.3%, and by a further 1.8% from pre-comp to comp phase; corresponding increases in 4-km mean power were 6.1% and 2.2% (90% likely limits all approximately +/-2.6%). The variabilities for peak and 4-km mean powers were 1.2%-1.8% for sessions separated by < or = 2 wk and 2.0%-2.3% for sessions in pre-comp and comp phases, but increased to 3.4%-3.8% for sessions between the base and other phases (likely limits approximately (x/)/(1.6). Individual differences in the improvement in performance after the base phase evidently produced the greater variability between the base and the other phases. Interventions that might produce small but worthwhile changes in performance over a period of weeks-months need to be researched in pre-comp and comp phases, when the variability is small.